Petals on the wind [videorecording (DVD)] - Andrews, V. C. (Virginia C.); Burstyn, Ellen, 1932-; Graham, Heather, 1970-; Bruce, Dylan, 1980-; Nash, Wyatt; Buntain, Bailey (Andrews, V. C. (Virginia C.). Dollanganger family series., 2014)
The Dollanganger family attempt to put their sordid past behind them. But, as they soon discover, certain secrets can't be left behind. When Cathy finds herself in an abusive relationship, Christopher and Cathy are forced to face their forbidden feelings. And as tragedy strikes again, Cathy returns to Foxworth Hall to confront her grandmother and seek revenge on her mother. Christopher runs to Cathy's side, and the two are determined to start over again; together.